Handbook of leadership theory and practice : an HBS centennial colloquium on advancing leadership - Nohria, Nitin, 1962-; Khurana, Rakesh, 1967- (Boston, Mass. : Harvard Business Press, 2010)
"The Handbook of Leadership Theory and Practice is based on the Harvard Business School Centennial Colloquium "Leadership: Advancing an Intellectual Discipline" and edited by HBS professors Nitin Nohria and Rakesh Khurana, this volume brings together the most important scholars from fields as diverse as psychology, sociology, economics, and history to take stock of what we know about leadership and to set an agenda for future research. This comprehensive volume explores leadership along many dimensions, including the development of leadership as a discipline, the contingencies leadership research needs to address if it is to develop as a subject, the nurturing of individual leaders, and the most critical problems facing practicing leaders today."--BOOK JACKET.
Advancing leadership theory and practice / Nitin Nohria and Rakesh Khurana -- When does leadership matter? : a contingent opportunities view of CEO leadership / Noam Wasserman, Bharat Anand, and Nitin Nohria -- Revisiting the meaning of leadership / Joel Podolny, Rakesh Khurana, and Marya L. Besharov -- What is this thing called leadership? / J. Richard Hackman -- Leadership through an organization behavior lens : a look at the last half-century of research / Mary Ann Glynn and Rich DeJordy -- Psychological perspectives on leadership / Jennifer A. Chatman and Jessica A. Kennedy -- A clinical approach to the dynamics of leadership and executive transformation / Manfred Kets de Vries and Elisabet Engellau -- Classical sociological approaches to the study of leadership / Mauro F. Guillén -- Economists' perspectives on leadership / Patrick Bolton, Markus K. Brunnermeier, and Laura Veldkamp -- An economic perspective on leadership / Mark. A. Zupan -- Leadership and history / Walter A. Friedman -- Power and leadership / Joseph S. Nye, Jr. -- Leadership and cultural context : a theoretical and empirical examination based on project GLOBE / Mansour Javidan ... [et al.] -- Women and leadership : defining the challenges / Robin J. Ely and Deborah L. Rhode -- A contingency theory of leadership / Jay Lorsch -- What is leadership? : the CEO's role in large, complex organizations / Michael E. Porter and Nitin Nohria -- What makes teams of leaders leadable? / Ruth Wageman and J. Richard Hackman -- Decision making as leadership foundation / Michael Useem -- Leading change : leadership, organization, and social movements / Marshall Ganz -- Leadership in a globalizing world / Rosabeth Moss Kanter -- Unlocking the slices of genius in your organization : leading for innovation / Linda A. Hill ... [et al.] -- Identity-based leader development / Herminia Ibarra, Scott Snook, and Laura Guillén Ramo -- The experience conundrum / Morgan W. McCall, Jr. -- Leadership development interven
Includes bibliographical references and index.
Description based on print version record.
Keywords: Leadership; Executive ability; International business enterprises; Executive ability; International business enterprises; Leadership; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books